Particular solution for anomalous diffusion equation with source term - Araujo, M. T. [UNESP]; Drigo Filho, Elso [UNESP] (Iop Publishing Ltd, 2011)
In literature the phenomenon of diffusion has been widely studied, however for nonextensive systems which are governed by a nonlinear stochastic dynamic, there are a few soluble models. The purpose of this study is to present the solution of the nonlinear Fokker-Planck equation for a model of potential with barrier considering a term of absorption. Systems of this nature can be observed in various chemical or biological processes and their solution enriches the studies of existing nonextensive systems.